Design Considerations for Macroencapsulation Devices for Stem Cell Derived Islets for the Treatment of Type 1 Diabetes. Issue 16 (21st June 2021) - Goswami, Debkalpa; Domingo‐Lopez, Daniel A.; Ward, Niamh A.; Millman, Jeffrey R.; Duffy, Garry P.; Dolan, Eimear B.; Roche, Ellen T.
Abstract: Stem cell derived insulin producing cells or islets have shown promise in reversing Type 1 Diabetes (T1D), yet successful transplantation currently necessitates long‐term modulation with immunosuppressant drugs. An alternative approach to avoiding this immune response is to utilize an islet macroencapsulation device, where islets are incorporated into a selectively permeable membrane that can protect the transplanted cells from acute host response, whilst enabling delivery of insulin. These macroencapsulation systems have to meet a number of stringent and challenging design criteria in order to achieve the ultimate goal of reversing T1D. In this progress report, the design considerations and functional requirements of macroencapsulation systems are reviewed, specifically for stem‐cell derived islets (SC‐islets), highlighting distinct design parameters. Additionally, a perspective on the future for macroencapsulation systems is given, and how incorporating continuous sensing and closed‐loop feedback can be transformative in advancing toward an autonomous biohybrid artificial pancreas. Abstract : Transplantation of stem‐cell‐derived islets (SC‐islets) is a promising treatment option for the reversal of Type 1 diabetes. This progress report reviews the design considerations and functional requirements for macroencapsulation systems, specifically for SC‐islets, highlighting distinct design parameters. Incorporating continuous sensing and closed‐loop feedback in future macroencapsulation systems could be transformative in advancing toward an autonomous biohybrid artificial pancreas.